Sistem Pakar Tes Kepribadian Menggunakan Metode Dempster-Shafer - Sri Wahyuni Sinaga (STMIK Budi Darma, 2021)
Personality is a pattern of human behavior that comes from within someone's self. personality sometimes needs to be adapted to the context in the world of employment, personality is often identified with the attitude and character of someone in the world of work and everyday life. Women who are considered to have a good personality can be seen from the way he walks, how to speak, and how to behave properly. The term personality comes from the Latin word